SpSoxB1 Serves an Essential Architectural Function in the Promoter SpAN, a tolloid/BMP1-Related Gene - Kenny, Alan P. (Gene Expr, 2018)
Transcription of SpAN, which encodes a secreted protease related to tolloid and BMP 1, is differentially regulated along the animal–vegetal axis of the sea urchin embryo by a maternally initiated mechanism. Regulatory sites that bind SpSoxB1 and CBF (CCAAT binding factor) are essential for strong transcriptional activity because mutations of these elements reduce promoter activity in vivo 20- and 10-fold, respectively. Here we show that multimerized SpSoxB1 elements cannot activate transcription from the SpAN basal promoter in vivo. However, like other factors containing HMG-class DNA binding domains, SpSoxB1 does induce strong bending of DNA. The CBF binding site lies abnormally far from the transcriptional start site at −200 bp. We show that the SpSoxB1 site is not required if the CCAAT element is moved 100 bp closer to the transcriptional start site, replacing the SpSoxB1 site. This supports a model in which the bending of SpAN promoter DNA by SpSoxB1 facilitates interactions between factors binding to upstream and downstream regulatory elements.